Strategies of Subtitling Egyptian Idiomatic Expressions and Proverbs into English - Reem Shuhaiber; Ahmad S. Haider (Universitat Jaume I. Department of English Studies, 2023)
Several platforms, such as Netflix, offer subtitles of different works and movies in several languages, including Arabic and English.  In this study, the researchers discuss the strategies used to overcome the challenges subtitlers face when translating Egyptian idiomatic expressions and proverbs into English. A parallel corpus of four movies, namely تيتا رهيبة  My horrible grandma, عسل أسود  Bittersweet, الباشا تلميذ  The Student cop, and عمارة يعقوبيان Yacoubian Building, was compiled from scratch. The idiomatic expressions and proverbs were identified and analyzed according to Baker's taxonomies (Baker, 1992). The translation strategy of "paraphrasing" was the most frequently used in translating proverbs. In rendering idiomatic expressions, the subtitlers mostly resorted to the strategy of "translating by paraphrasing using unrelated words to deal with the non-equivalent expression". "Mistranslation" was detected in some cases, most likely due to the lack of the target culture knowledge and not finding appropriate equivalents. The subtitlers sometimes used literal translation, which distorted the meaning and resulted in unnatural translations. The results also revealed that some expressions that were repeatedly used in the movies were translated differently according to the context. This study can be beneficial to translators and translation students, especially those interested in subtitling movies and translating proverbs and idiomatic expressions.